Effects of Tapping on the Holding Strength of Cancellous Bone Screws - Hearn, T. C.; Surowiak, J. F.; Schatzker, J. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
The purpose of the study was to determine whether tapping affects the holding strength of cancellous bone screws in soft material. Paired extraction tests were conducted using 6.5 mm cancellous bone screws in porous polyurethane foam. One member of each pair had a pre-tapped pilot hole, the other was inserted in a self-tapping manner. The maximum value of tensile force during extraction with a servohydraulic materials testing machine was recorded as the screw holding strength.Comparison of the holding strengths between the pre-tapped and self-tapping groups revealed a lower mean holding strength for the pre-tapped group (p <0.05). This result contrasts with previous studies which showed that pre-tapping increases the holding strength of bone screws in relatively stronger materials. The effect of tapping on the holding strength of bone screws is therefore dependant on the material properties of the host medium.This study examined the effect of tapping the pilot hole on the extraction strength of 6.5 mm cancellous bone screws in soft, synthetic cancellous material. In contrast with previous studies in stronger materials, it was found that tapping significantly reduces the holding strength of bone screws. The effects of tapping depend on the material properties of the host medium.
Keywords: Internal fixation; holding strength; cancellous bone screws